SENŲJŲ LIETUVIŠKŲ KNYGŲ RINKINYS SUOMIJOS NACIONALINĖJE BIBLIOTEKOJE HELSINKYJE - NAVICKIENĖ, AUŠRA (Knygotyra, 2011)
Vilniaus universiteto Knygotyros ir dokumentotyros institutas Universiteto g. 3, LT-01511 Vilnius, Lietuva El. paštas: ausra.navickiene@kf.vu.lt Straipsnyje nagrinėjamas lietuviškų knygų rinkinys Suomijos nacionalinėje bibliotekoje Helsinkyje, susiformavęs XIX amžiuje. Rinkinys apibūdinamas keliais aspektais: analizuojama jo teminė ir tipologinė sudėtis, rekonstruojama susidarymo istorija, apibrėžiama jame saugomų spaudos paminklų vertė ir reikšmė Lietuvos knygos ir knygininkystės paveldui bei jo tyrimams. Reikšminiai žodžiai: XIX a. lietuviškų knygų paminklai, Suomijos nacionalinė biblioteka, Lituanikos rinkiniai Europos nacionalinėse bibliotekose. COLLECTION OF OLD LITHUANIAN BOOKS AT FINNISH NATIONAL LIBRARY IN HELSINKY AUŠRA NAVICKIENĖ Abstract Even though Lithuanian publications of Helsinki University Library (now – Finnish National Library) are recorded in bibliographical publication and are known to organisers of Lithuanian retrospective bibliography series A “Books in Lithuanian language”, nevertheless these publications did not attract a special attention of book researchers yet. Professor Klemensas Sinkevičius when sharing his impressions about IFLA congress in Helsinki has mentioned this collection of Lithuanian books but he did not show deeper interest in it. If to take a deeper look it is obvious that even a small part of the collection (collection of Lithuanian old books) a few aspects of which were described in the article is worth of further investigation. This part of collection is valuable because of publications themselves that could be called monuments, as they are of rare publications category. Majority of them are unique because of their perfect physical condition or because of other criteria of value. The whole collection of Lithuanian books is also a monument because it is worth investigation phenomenon reflecting application of law on compulsory copy controlled by censorship in Lithuania at the time of tsars’ rule. In planning further research work it would be important to plan research of the whole Lithuanian book and Lithuania-related books collection that is in the Finnish National Library. The plan would consist of research of the publications as such de visu, a deeper analysis of history of formation of the collection, analysis of its composition in various aspects, preparation of a list of Lithuanian book-monuments, which could be a part of digital of European heritage and consideration of strategy and projects needed to implement it.